2014
DOI: 10.1080/09168451.2014.948374
|View full text |Cite
|
Sign up to set email alerts
|

The sole cysteine residue (Cys301) of tetrathionate hydrolase from Acidithiobacillus ferrooxidans does not play a role in enzyme activity

Abstract: Cysteine residues are absolutely indispensable for the reactions of almost all enzymes involved in the dissimilatory oxidation pathways of reduced inorganic sulfur compounds. Tetrathionate hydrolase from the acidophilic iron- and sulfur-oxidizing bacterium Acidithiobacillus ferrooxidans (Af-Tth) catalyzes tetrathionate hydrolysis to generate elemental sulfur, thiosulfate, and sulfate. Af-Tth is a key enzyme in the dissimilatory sulfur oxidation pathway in this bacterium. Only one cysteine residue (Cys301) has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
(46 reference statements)
0
8
0
Order By: Relevance
“…However, the three-dimensional structure was not obtained until now. It was reported that the sole cysteine residue (Cys301) in Af-TetH was involved in neither the tetrathionate hydrolysis reaction nor the subunit assembly, indicating a novel cysteine-independent reaction mechanism for this enzyme (Kanao et al, 2014).…”
Section: Thiosulfate Oxidationmentioning
confidence: 99%
“…However, the three-dimensional structure was not obtained until now. It was reported that the sole cysteine residue (Cys301) in Af-TetH was involved in neither the tetrathionate hydrolysis reaction nor the subunit assembly, indicating a novel cysteine-independent reaction mechanism for this enzyme (Kanao et al, 2014).…”
Section: Thiosulfate Oxidationmentioning
confidence: 99%
“…Some ordered water molecules were present at both edges of the cavities (two water molecules are highlighted by the black arrows in Figure 2b). Although cysteine residues are indispensable in the reactions of many enzymes of dissimilatory sulfur oxidation metabolism, we previously reported that the sole cysteine residue (Cys301) of Af ‐Tth is not involved in the hydrolysis reaction 22 . Cys301 was more than 25 Å from this cavity.…”
Section: Resultsmentioning
confidence: 95%
“…Recombinant Af ‐Tth was synthesized in E. coli as inclusion bodies in an inactive form. The active enzyme was refolded from inclusion bodies under acidic conditions and purified to homogeneity as a homodimer via gel‐permeation column chromatography (GPC) at pH 4.0 22 . The crystallization of Af ‐Tth was previously described in detail 23 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations